Reasoning about efficiency within a probabilistic μ-calculus - McIver, A (1999)
Expectation-based probabilistic predicate transformers [15] provide a logic for probabilistic sequential programs, giving access to expressions such as 'the probability that predicate A is achieved finally'. Using expectations more generally however, we can express μ-calculus formulae for the expected path-length of a computation tree. Moreover within an expectation-based μ-calculus such efficiency measures and more conventional (but probabilistic) temporal operators [14] can be related.